ANALISIS IMPLEMENTASI SISTEM TANGGAP DARURAT BERDASARKAN OHSAS 18001:2007 KLAUSUL 4.4.7 DI PT X KALIMANTAN SELATAN - Faeliskah Faeliskah; Bina Kurniawan; Suroto Suroto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
OHSAS 18001: 2007 has the objective to protect workers from the occurrence of an emergency. In the event of an emergency, the emergency response team had to perform first aid treatment on the spot, but the distance between the clinic with coal excavation area is quite remote and equipment of first aid box in the area are not yet available and there is no standby team of volunteers. The purpose of this study was to analyze the implementation of emergency response system based on OHSAS 18001: 2007 clause 4.4.7 in PT X South Kalimantan. The benefits of research as input and consideration of the company's emergency response system based on OHSAS 18001: 2007. This study is a qualitative descriptive study with field observations and in depth interviews. The results show there has been no emergency response team officers were on standby coal excavation area. The Company is already providing emergency facilities, but for the amount of first aid box and its contents still not appropriate. First aider in the company does not have a first aid license of the responsible government agency such as kemenaker. Emergency response team has BASARNAS license but the license is not valid. The audit results OHSAS 18001: 2007 in the company if there are findings then immediately followed up as in the company's procedures. Suggestions for PT X South Kalimantan is submitted to the leadership to appoint a field supervisor in each area of the excavation of coal for standby in the area as an first aider, providing first aid boxes in the post-security and area excavation of coal, filed licensing first aider to the leadership for members emergency response team, renew the license BASARNAS owned by the emergency response team.